Religion in the Press: The Construction of Religion in the Korean News Media - Cho, Kyuhoon (Journal of Korean religions, 2017)
This article concerns the configuration of religion in the media sector of modern Korea. With the globalization of the modern world, mass media have increasingly become a differentiated field of communication through which to process various understandings of the religious or the spiritual in any given society. This article focuses on how religion is presented in the news media such as newspapers and broadcasters in contemporary South Korea. Since the 1990s, the media industry in Korean society has rapidly turned into an autonomous profession as the nation-state has made great progress toward democracy and social reformation. In this new social context, a majority of media workers have internalized the standards of liberal or even progressive journalism. Reflecting on the socio-political shift, media professionals have actively produced information and assessments about different religious groups, many of which are concerned with cultural, anti-social, and sensational dimensions of religion. The author studies the underlying trends and logic in the media's articulation of religion, which are selectively intertwined with the secular and religious constellation of Korean society.